Kontestasi Kuasa Kepemimpinan Formal dengan Informal dalam Kebijakan Publik dan Politik Keseharian - Mayrudin, Yeby Ma'asan; Husna, Nabilla Amalia; Yuliati, Fanny Rosye (Jurusan Ilmu Politik Universitas Bangka Belitung, 2020)
This article discusses the dynamics of the contestation of the power of the village head as a formal leader with Abah Olot who is the traditional leader as an informal leader in public policies and daily politics in the traditional village of Guradog, Curugbitung District, Lebak Regency, Banten Province. The issue shows the existence of power contestation between actors. This intersection results in a battle of dominative power between the two actors. Therefore, the research team traced the practice of power relations that occurred to be able to be used as a reflection to explain the problematics. In investigating this phenomenon, the research team used the “Leadership” and “Shadow State” framework which was used as an analysis tool. The research method uses descriptive qualitative method. This type of method is able to manifest descriptive data related to the subject matter in this article. As a result, this paper proves the manifestation of the informal leader's hegemonic power of formal leadership. Shadow state practices of the power of informal actors who are able to